Definition of a rational surface mesh for mining equipment modeling in a DEM environment - Dubinkin D.M.; Yalyshev A.V. (Горное оборудование и электромеханика)
In mining, the discrete element method has found its application due to the ability to simulate individual particles of bulk material. The paper examines the influence of the dimension of the grid describing the surface of mining equipment on the accuracy of calculating contact pressures using the discrete element method (DEM). A brief description of the contact pressure calculation mechanism is provided. The methods of defining surfaces for modeling interactions with particles are given. Recommendations are given with justification and taking into account the experience of other researchers on the rational choice of a surface grid for solving various problems using modeling. As a result, the coefficient Ks/d was introduced, reflecting the ratio of the dimensional grid to the particle size. A number of coefficients have been selected for the Ks/d study.=4; 2; 1; 0,5; 0,25. A simulation with a different scale of the dimensional grid was carried out to study changes in the load distribution. Particles with the same properties corresponded to each grid. The simulation was carried out for spherical particles with point contact and cubic particles with area contact. As a result of the simulation, the distribution of contact pressure is determined for both spherical and cubic particles. As a result, a number of rational values of the ratio of the mesh dimension and particles were created, depending on the researcher's tasks, so Ks/d = 0.5...1 is the most versatile and allows you to evaluate both loads and wear of mining equipment surfaces, other ratios can also be applied in specific tasks.